Ferroelectric and Interlayer Co-optimization with In-depth Analysis for High Endurance FeFET - Zhou, Yuejia; Liang, Zhongxin; Luo, Wenpu; Yu, Ming; Zhu, Runteng; Lv, Xiao; Li, Jiachen; Huang, Qianqian; Liu, Fei; Tang, Kechao; Ru HUANG (2022 International Electron Devices Meeting (IEDM), 2022)
In face of the critical endurance issue, for the first time we take a holistic perspective to co-optimize the ferroelectric materials and interlayer in FeFET. Compared to the common HZO based gate stack, the novel combination of Hf0.95 Al0.05 O2+Al2 O3 enhances the endurance to $\gt 5 × 10 ^9$ cycles while maintaining a retention > 10 years. In-depth analysis based on DFT and DQSCV reveal the reduction of interlayer electric field and interface charge trapping as the mechanism of optimization. We also develop a distributed interface trap model to correlate different trapping dynamics with the interlayer property in each device. This work pushes forward the understanding and development of high endurance strategy for FeFET.